Surface Charge and Cellular Processing of Covalently Functionalized Multiwall Carbon Nanotubes Determine Pulmonary Toxicity - Li, Ruibin; Wang, Xiang; Ji, Zhaoxia; Sun, Bingbing; Zhang, Haiyuan; Chang, Chong Hyun; Lin, Sijie; Meng, Huan; Liao, Yu-Pei; Wang, Meiying; Li, Zongxi; Hwang, Angela A; et al. (ACS nano, 2013)
Functionalized carbon nanotubes (f-CNTs) are being produced in increased volume because of the ease of dispersion and maintenance of the pristine material physicochemical properties when used in composite materials as well as for other commercial applications. However, the potential adverse effects of f-CNTs have not been quantitatively or systematically explored. In this study, we used a library of covalently functionalized multiwall carbon nanotubes (f-MWCNTs), established from the same starting material, to assess the impact of surface charge in a predictive toxicological model that relates the tubes’ pro-inflammatory and pro-fibrogenic effects at cellular level to the development of pulmonary fibrosis. Carboxylate (COOH), polyethylene glycol (PEG), amine (NH2), sidewall amine (sw-NH2), and polyetherimide (PEI)-modified MWCNTs were successfully established from raw or as-prepared (AP-) MWCNTs and comprehensively characterized by TEM, XPS, FTIR, and DLS to obtain information about morphology, length, degree of functionalization, hydrodynamic size, and surface charge. Cellular screening in BEAS-2B and THP-1 cells showed that, compared to AP-MWCNTs, anionic functionalization (COOH and PEG) decreased the production of pro-fibrogenic cytokines and growth factors (including IL-1β, TGF-β1, and PDGF-AA), while neutral and weak cationic functionalization (NH2 and sw-NH2) showed intermediary effects. In contrast, the strongly cationic PEI-functionalized tubes induced robust biological effects. These differences could be attributed to differences in cellular uptake and NLRP3 inflammasome activation, which depends on the propensity toward lysosomal damage and cathepsin B release in macrophages. Moreover, the in vitro hazard ranking was validated by the pro-fibrogenic potential of the tubes in vivo. Compared to pristine MWCNTs, strong cationic PEI-MWCNTs induced significant lung fibrosis, while carboxylation significantly decreased the extent of pulmonary fibrosis. These results demonstrate that surface charge plays an important role in the structure–activity relationships that determine the pro-fibrogenic potential of f-CNTs in the lung.